A inserção da América do Sul no discurso diplomático brasileiro no Governo Lula (2003-2010) - Barbosa, Gabriela Gonçalves (2011)
Brazil's relations with the South America were not always considered a priority for Brazilian foreign policy. In reviewing some historical relationships of Brazil to its neighbors, we realize that during the 1990s begins to occur a shift in focus, especially after the accession of Mexico to NAFTA, followed by the proposed creation of the FTAA by the United States, financial crises and attacks of September 11, 2001, among others. At the end of the Cardoso government we realize the need to deepen political dialogue with South America, but it is only during the two terms of Luis Inacio Lula da Silva that this idea was widely supported and, in certain way, popularized. Based on it, this paper aims to discuss the importance attached to South America in Brazil's foreign policy from an analysis of the insertion of "South America" in the diplomatic discourse in Brazil during the Lula government. For this, we will analyze the official statements of President Lula between 2003 and 2010. The approach of modernist linguists when emphasizing the discourse and its power to construct the social reality is an inspiration, and at the end, we propose an analysis of inserting South America in Brazilian diplomatic discourse, starting from the idea of "model correction" and the development of the logistics paradigm - proposed by Cervo, and also the idea of "continuity of parameters of foreign policy" and the concept of presidential diplomacy - proposed by Danese. We realized that the consolidation of South America, for the Brazilian government, would be a key process in the quality of the international insertion of Brazil, where the challenge is to establish trust in political relations from a demonstrated Brazilian commitment in deepening South America s integration, through a process of knowledge and conviction that through acts of speech and direct relationship, the coordination between the countries of South America is of outstanding importance for a more effective participation in international forums.